High-corrosion-resistance cerium magnet and preparation method thereof

Through the combination of cerium alloy powder and grain boundary modified powder, combined with magnetic field orientation and high-temperature sintering, the problem of inconsistent sintering and magnetic properties of cerium magnets at high temperatures in the prior art is solved, and high density and corrosion resistance are achieved Cerium magnet production simplifies the process and reduces costs.

CN119296904APending Publication Date: 2025-01-10JING CI MATERIAL SCI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411303558.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art is difficult to mass-produce high corrosion-resistant cerium magnets at high temperatures, and their magnetic properties are inconsistent, which is prone to corrosion and coarse grains, resulting in high costs and difficult process control.

Method used

Using a combination of cerium alloy powder and grain boundary modified powder, a cerium magnet with high density and excellent magnetic properties is formed by magnetic field orientation molding and isostatic pressure, combined with high temperature sintering and tempering heat treatment.

Benefits of technology

The sintered cerium magnet at higher temperatures is achieved, reducing the coarse grains and corrosion phenomena, improving the corrosion resistance and magnetic properties of the magnets, simplifying the production process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119296904A_ABST
    Figure CN119296904A_ABST
Patent Text Reader

Abstract

The invention discloses a high-corrosion-resistance cerium magnet, the raw materials of the permanent magnet are cerium alloy powder and grain boundary modified powder, the adding mass proportion of the grain boundary modified powder is 0.5%-5%, and the microstructure comprises cerium magnet main phase grains, a grain boundary phase and a grain boundary modified phase; the component of the cerium alloy powder is (PrNd) aCebRE1cTMdFebalBe, and the component of the grain boundary modified powder is RE2a1Mb1Oc1Hd1Ce1. Compared with a cerium magnet with the same components produced by a conventional process, the high-corrosion-resistance cerium magnet disclosed by the invention has the advantages that the corrosion resistance degree is higher, the high-corrosion-resistance cerium magnet is suitable for high sintering temperature, the high-corrosion-resistance cerium magnet and other rare earth magnets can be easily sintered in the same furnace, and the magnetic performance consistency of the same batch of magnets is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of rare earth permanent magnet material preparation, and more specifically, to a highly corrosion-resistant cerium magnet and a preparation method thereof. Background Art

[0002] Rare earth permanent magnet materials are the type of permanent magnet materials with the highest coercivity and the largest magnetic energy product, and are key emerging strategic materials for the country. Sintered NdFeB is currently the rare earth permanent magnet material with the best comprehensive magnetic properties and the highest cost performance. Since its introduction in 1983, it has been widely used in the fields of automobiles, electronics, electric power, energy, medical treatment and information technology, and is known as the "King of Magnets" in the industry.

[0003] Neodymium iron boron (Nd-Fe-B) permanent magnet materials belong to the third generation of rare earth permanent magnet materials. They have excellent comprehensive magnetic properties and are widely used in electric vehicles, medical devices, wind power generation, aerospace, ships and other fields. With the vigorous development of new energy vehicles, smart devices and industrial robots, the demand and output of neodymium iron boron permanent magnet materials have increased year by year. my country has rich rare earth resources, and the Bayan Obo rare earth mine is the largest supply base of rare earth raw materials in my country. Rare earth elements have the characteristics of co-existence in the Bayan Obo mine, that is, lanthanum (La), cerium (Ce), praseodymium (Pr), and neodymium (Nd) coexist, with a content of La-28%, Ce-52%, Pr-5.1%, and Nd-14.7%. Neodymium iron boron materials mainly consume rare earth elements such as praseodymium (Pr) and neodymium (Nd) during production, while the low-priced co-existing La and Ce are piled up and idle.

[0004] In order to solve the problem of balanced utilization of rare earth resources and reduce the cost of NdFeB materials, it is necessary to develop and utilize cerium magnets. Studies have shown that the electrode potential of Nd element is -2.43V, while the electrode potential of Ce is -2.48V. The replacement of Nd by Ce will expand the potential difference between the main phase / grain boundary phase, causing cerium magnets (Ce-Fe-B) to be more susceptible to corrosion than neodymium magnets (Nd-Fe-B). On the other hand, Ce is easy to aggregate in the rare earth-rich grain boundary phase during phase formation, resulting in the coarsening of magnet grains. When corrosion occurs, the grains will fall off the magnet surface. The fall of Ce aggravates the further expansion of corrosion. In addition, the aggregation of Ce at the grain boundaries is often unevenly distributed, resulting in large fluctuations in the magnetic properties of cerium magnets in the same batch and greater difficulty in process control. In the current conventional production process, in order to avoid the problem of cerium magnet grains being too large, the sintering temperature of cerium magnets is often lower than that of neodymium magnets, resulting in the inability to sinter cerium magnets and neodymium magnets in the same furnace due to the different firing temperatures. It is necessary to increase the cost of heat treatment equipment specifically for the sintering of cerium magnets, and even if a lower sintering temperature is used, when the size of the main phase grains of the cerium alloy is small, the corrosion resistance of the cerium magnet is relatively poor.

[0005] In Chinese invention patent CN 108666065 A, a highly corrosion-resistant Ce-based permanent magnetic material and a preparation method thereof are disclosed. The material mainly uses spark plasma sintering to achieve rapid sintering to obtain a densified magnet, inhibit grain growth, and improve the corrosion resistance of the magnet. However, the spark plasma sintering process used in this scheme is relatively expensive, and the amount of furnace loading each time is very small. It is currently still an experimental device, and it is difficult to achieve batch preparation of cerium magnets. Therefore, it is necessary to propose a highly corrosion-resistant cerium magnet and a preparation method thereof, which can complete sintering at a higher temperature while having good corrosion resistance. Summary of the invention

[0006] An object of the present invention is to provide a highly corrosion-resistant cerium magnet and a preparation method thereof, which can improve the corrosion resistance of the cerium magnet, is suitable for high sintering temperatures, is easy to sinter in the same furnace with other types of rare earth magnets, and has excellent consistency in magnetic properties of the same batch of magnets, thereby enabling mass production.

[0007] In order to achieve these purposes and other advantages according to the present invention, according to one aspect of the present invention, the present invention provides a highly corrosion-resistant cerium magnet, the raw materials of the permanent magnet are cerium alloy powder and grain boundary modified powder, the added mass ratio of the grain boundary modified powder is 0.5% to 5%, and the microstructure of the highly corrosion-resistant cerium magnet includes cerium magnet main phase grains sintered from cerium alloy powder, grain boundary phase and grain boundary modified phase mixed in the grain boundary phase and sintered from grain boundary modified powder;

[0008] The composition of the cerium alloy powder is as follows by mass percentage: (PrNd) a Ce b RE 1 c TM d Fe bal B e , 0≤a≤30, 3≤b≤30, 0≤c≤5, 0≤d≤2, 0.8≤e≤1.1, bal is the margin, RE 1 is one or a combination of La, Y, Dy, Tb, Gd, and Ho, and TM is one or a combination of Cu, Al, Ga, Zr, Nb, Ti, and W;

[0009] The composition of the grain boundary modified powder is as follows by mass percentage: RE 2 a1 M b1 O c1 H d1 C e1 , where RE 2It is one or a combination of rare earth elements La, Ce, Y, Pr, Nd, Dy, Tb, Ho, and Gd, M is one or a combination of Fe, Co, Cu, Al, Nb, Zr, Ti, W, and B, O represents oxygen, H represents hydrogen, and C represents carbon, wherein 0≤a1≤99.5, 0≤b1≤99.5, 0.05≤c1≤0.5, 0≤d1≤0.5, 0.04≤e1≤0.5, and 98.5≤a1+b1≤99.5.

[0010] Preferably, the average particle size of the cerium alloy powder is 1 to 6 μm, and the average particle size of the grain boundary modified powder is 0.1 to 3 μm.

[0011] Preferably, the average grain size of the main phase grains of the cerium magnet is 3-10 μm.

[0012] Preferably, the high corrosion-resistant cerium magnet has a C content of 500 to 3000 ppm, an O content of 500 to 1000 ppm, and a H content of 0 to 20 ppm.

[0013] The present invention also provides a method for preparing a highly corrosion-resistant cerium magnet, comprising the following steps:

[0014] S1. The ingredients are prepared according to the mass ratio of the components of the cerium alloy powder, and after removing surface impurities, the proportioned raw materials are placed in a quick-setting sheeting furnace, and the liquid raw materials are poured on a water-cooled copper roller at 1400-1500° C. to obtain a cerium alloy quick-setting sheet with a thickness of 0.2-0.6 mm, wherein the C content in the cerium alloy quick-setting sheet is ≤200ppm, and the O content is ≤150ppm;

[0015] S2, adding the cerium alloy quick-solidification sheet into a hydrogen crushing furnace for coarse crushing to obtain cerium alloy coarse powder, and then adding it into a jet mill for further crushing to obtain cerium alloy powder;

[0016] S3, preparing grain boundary modified powder according to proportion;

[0017] S4, adding the grain boundary modified powder to the cerium alloy powder in proportion, and mixing them thoroughly and evenly, the mixing time is 2 to 10 hours; after the mixing is completed, let it stand for 2 to 4 hours;

[0018] S5, magnetic field orientation molding and isostatic pressing: the mixed cerium alloy powder is added to a magnetic field press for orientation molding, the orientation magnetic field is 1.5-2.5T, and then isostatic pressing is performed at a pressure of 150-300MPa and a holding time of 10-50s to obtain a cerium magnet green body;

[0019] S6. Sintering and tempering the cerium magnet green body.

[0020] Preferably, in step S2, the cerium alloy quick-setting sheet is added to a hydrogen crushing furnace for coarse crushing to obtain cerium alloy coarse powder, which is specifically achieved under the following conditions: hydrogen absorption temperature of 20-200°C, hydrogen absorption pressure of 0.08-0.5MPa, dehydrogenation temperature of 400-600°C, and dehydrogenation time of 4-10h. The particle size of the cerium alloy coarse powder after hydrogen crushing is 200-900μm, and the H content is ≤1500ppm.

[0021] Preferably, the specific process of step S3 is: according to RE 2 The obtained alloy is pulverized by high-energy ball milling or airflow milling ultrafine powder collector, and the obtained alloy powder is successively oxidized, hydrogenated, and mixed with a lubricant containing C to obtain a composition of RE 2 a1 M b1 O c1 H d1 C e1 Grain boundary modified powder.

[0022] Preferably, the step S6 comprises the following steps:

[0023] S6.1. Place the cerium magnet green body into a vacuum sintering furnace for sintering heat treatment. First, keep it at 200-400℃ for 1-4h for decarburization treatment, then keep it at 600-900℃ for 2-10h for dehydrogenation treatment, and finally carry out sintering densification treatment at 1020-1100℃ for 2-10h. Then, turn on the fan to fill in inert gas and cool it to below 200℃.

[0024] S6.2. Carry out the first tempering in a vacuum or inert gas atmosphere, keep it at 400-950℃ for 2-10h, and quickly cool it to below 70℃ before taking it out of the furnace; according to actual needs, carry out the second tempering, keep it at 400-950℃ for 2-10h, and quickly cool it to below 70℃ before taking it out of the furnace, and you can get a highly corrosion-resistant cerium magnet.

[0025] The present invention has at least the following beneficial effects:

[0026] 1) The cerium magnet prepared by the method of grain boundary modification of the present invention can be sintered at a higher temperature without the problem of coarse grains. The magnet obtained by this method has a higher density and fewer holes prone to corrosion;

[0027] 2) The grain boundary modified powder of the present invention can play a role in lubricating and anti-oxidation of the cerium alloy powder: the grain boundary modified powder contains a certain proportion of carbon-containing lubricant, which can play a role as a lubricant during the mixing process with the cerium alloy powder. The magnetic powder is coated with a layer of lubricant on the outside, which can also play an anti-oxidation effect. In addition, the remanence B of the high corrosion-resistant cerium magnet of the present invention is r and coercivity H cj All of them will be superior to the cerium magnets produced by existing methods;

[0028] 3) The cerium magnet of the present invention has lower production cost and simple process: Due to the grain boundary modification of the cerium magnet of the present invention, the problem of sintering at a lower temperature in the conventional process in order to alleviate the volatilization and precipitation of Ce in the cerium magnet at high temperature must be overcome. The active passivation of the grain boundary phase by the grain boundary modification avoids the volatilization and precipitation of the cerium element in the sintering stage. Therefore, in the production of the highly corrosion-resistant cerium magnet of the present invention, there is no need to specially prepare heat treatment equipment, and sintering densification can be completed in a shorter time, thereby reducing the production cost of the cerium magnet;

[0029] 4) The cerium magnet of the present invention has more excellent magnetic property consistency: the present invention achieves the beneficial effect of higher density of cerium magnet and less residual impurity elements such as COH in the magnet through grain boundary modification and sintering degassing process optimization.

[0030] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A schematic diagram of the microstructure of the highly corrosion-resistant cerium magnet of the present invention;

[0032] Figure 2 The present invention is a flow chart for preparing the highly corrosion-resistant cerium magnet;

[0033] Figure 3 This is the morphology of the cerium magnet after corrosion in Example 1 of the present invention;

[0034] Figure 4 This is the morphology of the cerium magnet after corrosion in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can implement the invention with reference to the description.

[0036] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.

[0037] The present invention provides a highly corrosion-resistant cerium magnet. The raw materials of the permanent magnet are cerium alloy powder and grain boundary modified powder. The added mass ratio of the grain boundary modified powder is 0.5% to 5%. The microstructure of the highly corrosion-resistant cerium magnet includes cerium magnet main phase grains 100 sintered from the cerium alloy powder, a grain boundary phase 200, and a grain boundary modified phase 300 mixed in the grain boundary phase 200 and sintered from the grain boundary modified powder. The components of the cerium alloy powder are as follows by mass percentage: (PrNd) a Ce b RE 1 c TM d Fe bal B e , 0≤a≤30, 3≤b≤30, 0≤c≤5, 0≤d≤2, 0.8≤e≤1.1, bal is the margin, RE 1 is one or a combination of La, Y, Dy, Tb, Gd, and Ho, and TM is one or a combination of Cu, Al, Ga, Zr, Nb, Ti, and W; the composition of the grain boundary modified powder is as follows in terms of mass percentage: RE 2 a1 M b1 O c1 H d1 C e1 , where RE 2 It is one or a combination of rare earth elements La, Ce, Y, Pr, Nd, Dy, Tb, Ho, and Gd, M is one or a combination of Fe, Co, Cu, Al, Nb, Zr, Ti, W, and B, O represents oxygen, H represents hydrogen, and C represents carbon, wherein 0≤a1≤99.5, 0≤b1≤99.5, 0.05≤c1≤0.5, 0≤d1≤0.5, 0.04≤e1≤0.5, and 98.5≤a1+b1≤99.5.

[0038] Compared with neodymium magnets, cerium magnets have poor corrosion resistance because Ce is more active than Nd and tends to be unevenly enriched in grain boundaries. The present invention combines grain boundary modification with sintering process optimization to achieve a reduction in the potential difference between the main phase grains 100 and the grain boundary phases 200 of the cerium magnet and an increase in the density of the cerium magnet, thereby significantly improving the corrosion resistance of the manufactured cerium magnet. The grain boundary modified phase 300 formed by the grain boundary modified powder used in the present invention contains elements such as carbon, oxygen, and hydrogen, which have lower activity and higher corrosion potential than the grain boundary phase 200, thereby reducing the potential difference between the main phase grains 100 and the grain boundary phase 200 of the cerium magnet, reducing the driving force for spontaneous corrosion of the cerium magnet, and in addition, the grain boundary modified phase 300 It plays a passivating role in the grain boundary phase 200, reduces the fluidity of the grain boundary phase 200 at high temperature, so that the cerium magnet can be sintered at a higher temperature without the main phase grains 100 of the cerium magnet being prone to coarsening. The cerium magnet obtained by this method has a higher density, and the number of holes prone to corrosion is less. The ratio of the measured density to the theoretical density is ≥99.5%. At the same time, it can be sintered at a higher temperature and the consistency of the same batch is better. Specifically, compared with conventional cerium magnets with the same cerium content, the high corrosion-resistant cerium magnet of the present invention has a weight loss of 30% to 90% under the test conditions of 120°C, 100% RH, and 48h, and the sintering insulation temperature can be increased by 15 to 50°C. The residual magnetism B is tested by sampling at 9 points in the same furnace. r Fluctuation is ±70Gs, coercivity H cj Fluctuation is ±300Oe, squareness H k / H cj Fluctuation ±0.8%, with the advantages of good corrosion resistance, higher sintering temperature and stronger consistency of magnets in the same batch.

[0039] In another technical solution, the average particle size of the cerium alloy powder is 1 to 6 μm, and the average particle size of the grain boundary modified powder is 0.1 to 3 μm. During the pressing and sintering process, the cerium magnet green body will inevitably be slightly oxidized. Since the grain boundary modified powder has a fine particle size and higher activity than the cerium alloy powder, the oxygen element preferentially combines with the grain boundary modified powder, thereby avoiding oxidation of the main phase of the cerium alloy. Therefore, the remanent magnetism B of the high corrosion resistant cerium magnet of the invention is r and coercivity H cj They will be superior to the cerium magnets produced by existing methods.

[0040] In another technical solution, the average grain size of the main phase grains of the cerium magnet is 3 to 10 μm.

[0041] In another technical solution, the C content of the high corrosion-resistant cerium magnet is 500-3000 ppm; the O content is 500-1000 ppm, and the H content is 0-20 ppm.

[0042] like Figure 2 As shown, the present invention also provides a method for preparing a highly corrosion-resistant cerium magnet, comprising the following steps:

[0043] S1. The ingredients are prepared according to the mass ratio of the components of the cerium alloy powder, and after removing surface impurities, the proportioned raw materials are placed in a quick-setting sheeting furnace, and the liquid raw materials are poured on a water-cooled copper roller at 1400-1500° C. to obtain a cerium alloy quick-setting sheet with a thickness of 0.2-0.6 mm, wherein the C content in the cerium alloy quick-setting sheet is ≤200ppm, and the O content is ≤150ppm;

[0044] S2, adding the cerium alloy quick-solidification sheet into a hydrogen crushing furnace for coarse crushing to obtain cerium alloy coarse powder, and then adding it into a jet mill for further crushing to obtain cerium alloy powder;

[0045] S3, preparing grain boundary modified powder according to proportion;

[0046] S4, adding the grain boundary modified powder to the cerium alloy powder in proportion, and mixing them thoroughly and evenly, the mixing time is 2 to 10 hours; after the mixing is completed, let it stand for 2 to 4 hours;

[0047] S5, magnetic field orientation molding and isostatic pressing: the mixed cerium alloy powder is added to a magnetic field press for orientation molding, the orientation magnetic field is 1.5-2.5T, and then isostatic pressing is performed at a pressure of 150-300MPa and a holding time of 10-50s to obtain a cerium magnet green body;

[0048] S6. Sintering and tempering the cerium magnet green body.

[0049] In another technical solution, in step S2, the cerium alloy quick-setting sheet is added into a hydrogen crushing furnace for coarse crushing to obtain cerium alloy coarse powder, which is specifically achieved under the following conditions: hydrogen absorption temperature is 20-200°C, hydrogen absorption pressure is 0.08-0.5MPa, dehydrogenation temperature is 400-600°C, and dehydrogenation time is 4-10h; the particle size of the cerium alloy coarse powder after hydrogen crushing is 200-900μm, and the H content is ≤1500ppm.

[0050] In another technical solution, the specific process of step S3 is: according to RE 2 The obtained alloy is pulverized by high-energy ball milling or airflow milling ultrafine powder collector, and the obtained alloy powder is successively oxidized, hydrogenated, and mixed with a lubricant containing C to obtain a composition of RE 2 a1 M b1 O c1 H d1 C e1 Grain boundary modified powder.

[0051] In another technical solution, step S6 includes the following steps:

[0052] S6.1. Place the cerium magnet green body into a vacuum sintering furnace for sintering heat treatment. First, keep it at 200-400℃ for 1-4h for decarburization treatment, then keep it at 600-900℃ for 2-10h for dehydrogenation treatment, and finally sinter and densify it at 1020-1100℃ for 2-10h. Then, turn on the fan to fill in inert gas and cool it to below 200℃.

[0053] S6.2. Carry out the first tempering in a vacuum or inert gas atmosphere, keep it at 400-950℃ for 2-10h, and quickly cool it to below 70℃ before taking it out of the furnace; according to actual needs, carry out the second tempering, keep it at 400-950℃ for 2-10h, and quickly cool it to below 70℃ before taking it out of the furnace, and you can get a highly corrosion-resistant cerium magnet.

[0054] Specific examples are provided below to further illustrate the highly corrosion-resistant cerium magnet and the preparation method thereof provided by the present invention.

[0055] Example 1

[0056] S1: Press (PrNd) 18.5 Ce 10 Dy 0.3 Al 0.2 Cu 0.3 Ga 0.2 Ti 0.1 Fe bal B 0.89 The ingredients are mixed, the required raw materials are sandblasted to remove impurities such as surface oxide scale, and then the mixed raw materials are placed in a quick-setting sheeting furnace. The liquid raw materials are poured on a water-cooled copper roller at 1460°C to obtain a cerium alloy quick-setting sheet with an average thickness of 0.35mm. The C content of the cerium alloy quick-setting sheet is 98ppm and the O content is 96ppm.

[0057] S2: The cerium alloy quick-solidified sheet is added to the hydrogen crushing furnace for coarse crushing, the hydrogen absorption temperature is 100°C, the hydrogen absorption pressure is 0.10MPa, the dehydrogenation temperature is 400°C, the dehydrogenation time is 10h, the coarse powder particle size after hydrogen crushing is 500μm, and the H content is 1150ppm. Then the hydrogenated coarse powder is added to the air flow mill for re-crushing to obtain a cerium alloy powder with an average particle size of 4.0μm.

[0058] S3: Use vacuum melting furnace to melt Nd 90 Cu 10 The alloy was then milled using high energy ball milling with a ball to material ratio of 20:1 to obtain Nd 90 Cu 10The alloy was crushed and powdered to obtain Nd with an average particle size of 2.5 μm. 90 Cu 10 powder;

[0059] The obtained Nd 90 Cu 10 The powder was oxidized for 1 hour, and 1000 ppm of oxygen was added to the powder to obtain Nd 89.9 Cu 10 O 0.1 powder;

[0060] The obtained Nd 89.9 Cu 10 O 0.1 The powder was placed in a pressure vessel for hydrogen absorption treatment. The treatment time was 0.5 h. 2000 ppm of hydrogen was absorbed into the powder to obtain Nd 89.7 Cu 10 O 0.1 H 0.2 powder;

[0061] Nd 89.7 Cu 10 O 0.1 H 0.2 The powder is mixed with a carbonaceous lubricant to obtain a mass composition of Nd 89.4 Cu 10 O 0.1 H 0.2 C 0.3 Grain boundary modified powder.

[0062] S4: adding the grain boundary modified powder obtained in S3 to the cerium alloy powder obtained in S2 at a mass ratio of 1%, and then fully mixing the powders for 2 hours; after the powder mixing is completed, the mixture is allowed to stand for 2 hours.

[0063] S5: Magnetic field orientation molding and isostatic pressing: The uniformly mixed alloy powder is added into a magnetic field press for orientation molding, the orientation magnetic field is 1.5T, and then isostatic pressing is performed with a pressure of 150MPa and a holding time of 10s to obtain a cerium magnet green body.

[0064] S6: Sintering and tempering heat treatment:

[0065] S6.1: Place the cerium magnet green body into a vacuum sintering furnace for sintering heat treatment, firstly keep it at 400℃ for 1h for decarburization treatment, then keep it at 800℃ for 2h for dehydrogenation treatment, and finally carry out sintering densification treatment at 1040℃ for 4h, then fill it with argon gas and turn on the fan, and then cool it to below 200℃ for tempering treatment;

[0066] S6.2: In a vacuum atmosphere, keep the temperature at 770°C for 3 hours, then quickly cool to below 200°C; then heat to 600°C and keep for 3 hours, then quickly cool to below 70°C and take out of the furnace to obtain a highly corrosion-resistant cerium magnet.

[0067] Comparative Example 1

[0068] Prepare (PrNd) by the same process as in Example 1 18.5 Ce 10 Dy 0.3 Al 0.2 Cu 0.3 Ga 0.2 Ti 0.1 Fe bal B 0.89 The cerium alloy flakes and cerium alloy powders (S1 and S2 in Example 1) with the same composition are prepared, and only 0.25% of lubricant is added to the cerium alloy powders, followed by magnetic field orientation molding and isostatic pressing: the uniformly mixed alloy powders are added to a magnetic field press for orientation molding, the orientation magnetic field is 1.5T, and then isostatic pressing is performed at a pressure of 150MPa and a holding time of 10s to obtain a cerium magnet green body (S5 in Example 1);

[0069] The cerium magnet green body is placed in a vacuum sintering furnace for sintering heat treatment. First, it is kept at 400℃ for 1 hour for decarburization treatment, then kept at 800℃ for 2 hours for dehydrogenation treatment, and finally sintered at 1020℃ for densification treatment. The holding time is 4 hours, and then argon gas is filled and the fan is turned on. After cooling to below 200℃, tempering treatment is performed;

[0070] In a vacuum atmosphere, the temperature is kept at 770°C for 3 hours, and then quickly cooled to below 200°C; the temperature is then raised to 600°C and kept for 3 hours, and then quickly cooled to below 70°C before being taken out of the furnace to obtain a cerium magnet.

[0071] The magnets prepared in Example 1 and Comparative Example 1 were subjected to a magnet weight loss test (120°C, 100% RH, 48h), a corrosion resistance test (3.5% NaCl solution), and a demagnetization curve test (measurement method according to GB / T 3217-2013 and IEC60404-5), respectively. Sampling was performed at 9 points in the sintering furnace for magnetic property testing. The sampling positions were in the front, middle and back 3 temperature zones, and the upper, middle and lower 3 points were selected. The test results are shown in Tables 1 and 2.

[0072] Table 1 Comparison of corrosion resistance and impurity elements between Example 1 and Comparative Example 1

[0073]

[0074] Table 2 Comparison of magnetic properties and density uniformity between Example 1 and Comparative 1

[0075]

[0076] It can be found from the test data in Table 1 that the cerium magnet of Example 1 has the excellent characteristics of low weight loss and low corrosion potential compared with Comparative Example 1. At the same time, although the sintering temperature (1040°C) of Example 1 is 20°C higher than that of Comparative Example 1, the size of the main phase grains 100 of the cerium magnet of the final magnet is 1.6μm smaller than that of Comparative Example 1, indicating that the addition of grain boundary modified powder to form a grain boundary modified phase 300 in the grain boundary phase 200 reduces the fluidity of the grain boundary phase 200 at high temperature, allowing the cerium alloy powder to be sintered at a higher temperature. Coarse grains do not occur. By comparing the C and O elements of the magnets in Example 1 and Comparative Example 1, it is found that the O content of the magnet in Example 1 is slightly higher than that in Comparative Example 1. This is because the grain boundary modified powder has been oxidized, so that the final magnet retains part of the O element. The presence of this part of O element makes the grain boundary modified phase 300 passivate the grain boundary phase 200. The C content of the two magnets in Example 1 and Comparative Example 1 is slightly different, indicating that the carbon element of the cerium magnet green body is effectively removed through the decarburization and insulation platform in the sintering stage.

[0077] As shown in Table 2, by comparing the 9-point sampling tests of the two cerium magnet furnaces, it can be found that at the same sampling position, the residual magnetism B of Example 1 is r , coercive force H cj , Squareness H k / H cj and density are greater than those of comparative example 1. At the same time, the cerium magnets sampled at different positions in the furnace of Example 1 have smaller ranges (fluctuations) of various performance indicators, indicating that the addition of grain boundary modified powder and higher temperature sintering of the present invention can improve batch consistency while keeping the grain size small.

[0078] Figure 3 , Figure 4 The morphologies of the cerium magnets prepared in Example 1 and Comparative Example 1 after corrosion tests are compared. It can be found that Example 1 ( Figure 3 ) has fewer grains falling off on the magnet surface, so it has a smaller weight loss after corrosion and has higher corrosion resistance. Figure 4 ) It can be seen that more grains have fallen off and the corrosion is more serious, so the weight loss is large and the corrosion resistance is poor. The essential reason for the difference between the two is that by adding grain boundary modified powder, the grain boundary modified phase 300 is mixed into the grain boundary phase 200, thereby reducing the corrosion potential between the main phase grains 100 of the cerium magnet and the grain boundary phase 200. At the same time, the high corrosion-resistant cerium magnet in the present invention has smaller main phase grains 100 of the cerium magnet and higher density. There are fewer pores inside the high corrosion-resistant cerium magnet, so there are fewer channels for corrosion.

[0079] Example 2

[0080] S1: Press Nd3Ce 30 Al 0.1 Cu 0.253 Zr 0.1 Fe bal B 0.92 The ingredients are mixed, the required raw materials are sandblasted to remove impurities such as surface oxide scale, and then the mixed raw materials are put into a quick-setting sheet furnace. The liquid raw materials are poured on a water-cooled copper roller at 1420°C to obtain a cerium alloy quick-setting sheet with an average thickness of 0.6 mm. The C content in the cerium alloy quick-setting sheet is 200ppm, and the O content is 150ppm.

[0081] S2: The cerium alloy quick-solidification sheet is added to the hydrogen crushing furnace for coarse crushing, the hydrogen absorption temperature is 20°C, the hydrogen absorption pressure is 0.50MPa, the dehydrogenation temperature is 400°C, and the dehydrogenation time is 5h. The coarse powder after hydrogen crushing has a particle size of 800μm and a H content of 1200ppm. Then the hydrogenated coarse powder is added to the air flow mill for re-crushing to obtain a cerium alloy powder with a powder particle size of 6.0μm.

[0082] S3: Prepare Cu powder with an average particle size of 0.5 μm, and then oxidize and carbonize the Cu powder in sequence to obtain a Cu powder with a mass composition percentage of 99.4 O 0.1 C 0.5 Grain boundary modified powder.

[0083] S4: The grain boundary modified Cu obtained in step S3 99.4 O 0.1 C 0.5 Nd3Ce obtained by adding S2 to powder 30 Al 0.1 Cu 0.253 Zr 0.1 Fe bal B 0.92 The cerium alloy powder is added in a mass ratio of 2%, and then fully mixed for 4 hours; after the powder mixing is completed, it is allowed to stand for 2 hours before entering the next process.

[0084] S5: Add the uniformly mixed alloy powder into a magnetic field press for orientation molding, the orientation magnetic field is 1.8T, and then perform isostatic pressing, the pressure is 250MPa, and the holding time is 20s to obtain a cerium magnet green body.

[0085] S6.1: Place the green body into a vacuum sintering furnace for sintering heat treatment. First, keep it at 400℃ for 1h for decarburization treatment, then keep it at 800℃ for 2h for dehydrogenation treatment, and finally carry out sintering densification treatment at 1025℃ for 3h. Then fill it with argon and turn on the fan. After cooling to below 200℃, temper it.

[0086] S6.2: The tempering heat treatment process is: in a vacuum atmosphere, keep the temperature at 600℃ for 3 hours, quickly cool to below 70℃ and take out of the furnace to obtain a highly corrosion-resistant cerium magnet.

[0087] Comparative Example 2

[0088] Prepare Nd3Ce with the same composition as in Example 2 30 Al 0.1 Cu 0.253 Zr 0.1 Fe bal B 0.92 The cerium magnet is subjected to the steps of rapid solidification sheeting - powder making - magnetic field orientation molding - isostatic pressing - sintering and tempering, wherein the process is completely consistent with that of Example 2, the only difference being that the grain boundary modified powder is not added in Example 2.

[0089] The cerium magnets prepared in Example 2 and Comparative Example 2 were subjected to magnetic property tests, including a magnet weight loss test (120°C, 100% RH, 48h), a corrosion resistance test (3.5% NaCl solution), and a demagnetization curve test (measurement method according to GB / T3217-2013 and IEC 60404-5). The test results are shown in Table 3.

[0090] Table 3 Magnetic properties and other test results of cerium magnets in Example 2 and Comparative Example 2

[0091]

[0092] It can be seen from Table 3 that when Ce=30% and the sintering process is the same, the average particle size of the main phase grains 100 of the cerium magnet in Example 2 of the present invention is much smaller than that in Comparative Example 2, and the density is 0.07 g / cm higher than that in Comparative Example 2. 3 At the same time, the weight loss is nearly 30% lower than that of comparative example 2. At the same time, the magnetic properties of the cerium magnet of Example 2 are far superior to those of the magnet of comparative example 2 with the same composition and sintering process, indicating that the fluidity of the grain boundary phase 200 at high temperature can be effectively reduced by adding grain boundary modified powder to form a grain boundary modified phase 300 in the grain boundary phase 200. The grain boundary modified phase 300 plays a passivating role in the grain boundary phase 200 to avoid the situation where the main phase grains 100 of the cerium magnet are too large under high temperature sintering. Moreover, since the oxygen element preferentially combines with the grain boundary modified powder during the pressing and sintering process, the oxidation of the main phase grains 100 of the cerium magnet is avoided to a certain extent. The remanent magnetism B of the cerium magnet of Example 2 r and coercivity H cj All are better than Comparative Example 2.

[0093] Example 3

[0094] S1: Press (PrNd)27 La1Ce2Al 0.3 Cu 0.2 Zr 0.2 Fe bal B 0.95 The raw materials required above are sandblasted to remove impurities such as surface oxide scale, and then the raw materials with good proportion are put into a quick-setting sheet-throwing furnace, and the liquid raw materials are poured on a water-cooled copper roller at 1470°C to obtain a cerium alloy quick-setting sheet with an average thickness of 0.28mm, in which the C content is 90ppm and the O content is 70ppm.

[0095] S2: The cerium alloy quick-solidification sheet is added to the hydrogen crushing furnace for coarse crushing, the hydrogen absorption temperature is 200℃, the hydrogen absorption pressure is 0.10MPa, the dehydrogenation temperature is 480℃, and the dehydrogenation time is 7h. The coarse powder after hydrogen crushing has a particle size of 200μm and a H content of 1100ppm. Then the hydrogenated coarse powder is added to the air flow mill for re-crushing to obtain cerium alloy powder with a powder particle size of 3.5μm.

[0096] S3: Take out the magnetic powder from the super powder recovery tank of the jet mill. After testing, the composition of the magnetic powder is (PrNd) 38 (CuCoAlZrNbGa) 0.6 Fe 60.52 B 0.88 The average particle size of the powder is 1.5 μm. The powder is subjected to oxidation, hydrogenation and carbonization treatments in sequence to obtain a grain boundary modified powder, the mass percentage of which is (PrNd) 37 (CuCoAlZrNbGa) 0.6 Fe 60.52 Fe bal B 0.88 O 0.3 H 0. 2C 0.5 .

[0097] S4: adding the grain boundary modified powder obtained in S3 to the cerium alloy powder obtained in S2 at a mass ratio of 5%, and then fully mixing them for 4 hours; after the powder mixing is completed, standing for 2 hours, and then transferring to the next process.

[0098] S5: Magnetic field orientation molding and isostatic pressing: The uniformly mixed alloy powder is added into a magnetic field press for orientation molding, the orientation magnetic field is 1.8T, and then isostatic pressing is performed with a pressure of 250MPa and a holding time of 20s to obtain a cerium magnet green body.

[0099] S6: Sintering and tempering heat treatment:

[0100] S6.1: Place the green body into a vacuum sintering furnace for sintering heat treatment. First, keep it at 400℃ for 1h for decarburization treatment, then keep it at 800℃ for 2h for dehydrogenation treatment, and finally carry out sintering densification treatment at 1055℃ for 8h. Then fill it with argon and turn on the fan. After cooling to below 150℃, temper it.

[0101] S6.2: The tempering heat treatment process is: in a vacuum atmosphere, keep the temperature at 900°C for 3 hours, quickly cool to below 70°C, then heat to 500°C and keep for 6 hours, then quickly cool to below 70°C and take out of the furnace to obtain a highly corrosion-resistant cerium magnet.

[0102] Comparative Example 3

[0103] Prepare (PrNd) according to the same composition as Example 3 27 La1Ce2Al 0.3 Cu 0.2 Zr 0.2 Fe bal B 0.95 The cerium magnet is subjected to the steps of rapid solidification sheeting - powder making - magnetic field orientation molding - isostatic pressing - sintering and tempering, wherein the process is completely consistent with that of Example 3, the only difference being that the grain boundary modified powder is not added in Example 3.

[0104] The cerium magnets prepared in Example 3 and Comparative Example 3 were subjected to magnet weight loss tests (120°C, 100% RH, 48h), and samples were taken at 9 points in the sintering furnace and magnetic properties tests were performed to obtain the extreme values ​​(fluctuations) of various performance indicators. The test results are shown in Table 4.

[0105] Table 4 Magnetic properties and other test results of cerium magnets of Example 3 and Comparative Example 3

[0106]

[0107] It can be seen from Table 4 that compared with Comparative Example 3, the average particle size of the cerium alloy main phase grains in Example 3 with the addition of grain boundary modified powder is smaller, the density is larger, the weight loss ratio is much better than that in Comparative Example 3, and the extreme difference (fluctuation) of various performance indicators of cerium magnets produced in the same batch is smaller, and the batch consistency is far better than that in Comparative Example 3.

[0108] Example 4

[0109] S1: Press (PrNd) 15 Ce 15 Al 0.3 Cu 0.2 Zr 0.2 B 0.95The raw materials required above are sandblasted to remove impurities such as surface oxide scale, and then the raw materials with good proportion are put into the quick-setting sheeting furnace. The liquid raw materials are poured on the water-cooled copper roller at 1460℃ to obtain the cerium alloy quick-setting sheet with an average thickness of 0.25mm. The C content in the cerium alloy quick-setting sheet is 95ppm and the O content is 78ppm.

[0110] S2: The cerium alloy quick-solidification sheet is added to the hydrogen crushing furnace for coarse crushing, the hydrogen absorption temperature is 200°C, the hydrogen absorption pressure is 0.10MPa, the dehydrogenation temperature is 480°C, the dehydrogenation time is 7h, and the coarse powder particle size after hydrogen crushing is 200μm, and the H content is 1100ppm. Then the hydrogenated coarse powder is added to the air flow mill for re-crushing to obtain cerium alloy powder, and the average particle size of the powder is 3.5μm.

[0111] S3: using (PrNd) with an average particle size of 1.5μm 38 (CuCoAlZrNbGa) 0.6 Fe 60.52 B 0.88 Alloy powder, the alloy powder is subjected to oxidation, hydrogenation and carbonization treatment in sequence to obtain a mass percentage of (PrNd) 37 (CuCoAlZrNbGa) 0.6 Fe 60.52 B 0.88 O 0.3 H 0.2 C 0.5 Grain boundary modified phase powder.

[0112] S4: Add the grain boundary modified powder obtained in S3 to the cerium alloy powder obtained in S2, with the addition ratios being 0%, 1%, 2%, 3%, 4%, and 5% respectively, and then mix them thoroughly and evenly. The mixing time is 4 hours. After the mixing is completed, let it stand for 2 hours before proceeding to the next process.

[0113] S5: Magnetic field orientation molding and isostatic pressing: The uniformly mixed alloy powder is added into a magnetic field press for orientation molding, the orientation magnetic field is 1.8T, and then isostatic pressing is performed with a pressure of 250MPa and a holding time of 20s to obtain a cerium magnet green body.

[0114] S6.1: Place the cerium magnet green body into a vacuum sintering furnace for sintering heat treatment. First, keep it at 400℃ for 1h for decarburization treatment, then keep it at 800℃ for 2h for dehydrogenation treatment, and finally carry out sintering densification treatment at 1020-1100℃ for 8h. Then fill it with argon and turn on the fan. After cooling to below 150℃, tempering treatment is carried out. The sintering temperature of the magnet is adjusted accordingly according to the different addition ratios.

[0115] S6.2: In a vacuum atmosphere, keep the temperature at 900°C for 3 hours, quickly cool to below 70°C, then heat to 500°C and keep for 6 hours, then quickly cool to below 70°C and take out of the furnace to obtain a highly corrosion-resistant cerium magnet.

[0116] The grain size of each group of samples was observed using a scanning electron microscope, and the average grain size of about 6 μm was recorded as the optimal sintering temperature of the group of samples. The demagnetization curve of the sample was tested using NIM-6500C to obtain the magnetic properties of the sample. The density of the sample was obtained using the drainage method.

[0117] Table 5 Performance test of magnets with different addition amounts of grain boundary modified powder

[0118]

[0119] As shown in Table 5, by adding grain boundary modified powder to cerium alloy powder with the same composition, the weight loss ratio of the produced cerium magnet can be greatly reduced, and the density can be greatly increased, indicating that the corrosion resistance of the cerium magnet can be effectively improved by adding grain boundary modified powder. As can be seen from Table 5, the magnetic properties of the cerium magnet with added grain boundary modified powder are better than those of the cerium magnet without added grain boundary modified powder. Moreover, since the optimal sintering temperature of the cerium magnet after adding grain boundary modified powder is higher, it can be sintered in the same batch as the neodymium magnet during the production process of the cerium magnet, without the need for separate sintering equipment, which greatly saves the production cost of the cerium magnet.

[0120] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and the embodiments. It can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily realized. Therefore, without departing from the general concept defined by the claims and equivalent scope, the present invention is not limited to the specific details and the illustrations shown and described here.

Claims

1. Highly corrosion-resistant cerium magnet, characterized in that: The raw materials of the permanent magnet are cerium alloy powder and grain boundary modified powder, the added mass ratio of the grain boundary modified powder is 0.5% to 5%, and the microstructure of the highly corrosion-resistant cerium magnet comprises cerium magnet main phase grains (100) sintered from the cerium alloy powder, a grain boundary phase (200), and a grain boundary modified phase (300) mixed in the grain boundary phase (200) and sintered from the grain boundary modified powder; The composition of the cerium alloy powder is as follows by mass percentage: (PrNd) a Ce b RE 1 c TM d Fe bal B e , 0≤a≤30, 3≤b≤30, 0≤c≤5, 0≤d≤2, 0.8≤e≤1.1, bal is the margin, RE 1 is one or a combination of La, Y, Dy, Tb, Gd, and Ho, and TM is one or a combination of Cu, Al, Ga, Zr, Nb, Ti, and W; The composition of the grain boundary modified powder is as follows by mass percentage: RE 2 a1 M b1 O c1 H d1 C e1 , where RE 2 It is one or a combination of La, Ce, Y, Pr, Nd, Dy, Tb, Ho, and Gd, M is one or a combination of Fe, Co, Cu, Al, Nb, Zr, Ti, W, and B, O represents oxygen, H represents hydrogen, and C represents carbon, wherein 0≤a1≤99.5, 0≤b1≤99.5, 0.05≤c1≤0.5, 0≤d1≤0.5, 0.04≤e1≤0.5, and 98.5≤a1+b1≤99.

5.

2. The highly corrosion-resistant cerium magnet according to claim 1, characterized in that: The average particle size of the cerium alloy powder is 1 to 6 μm, and the average particle size of the grain boundary modified powder is 0.1 to 3 μm.

3. The highly corrosion-resistant cerium magnet according to claim 2, characterized in that: The average particle size of the main phase grains (100) of the cerium magnet is 3 to 10 μm.

4. The highly corrosion-resistant cerium magnet according to claim 1, characterized in that: The C content of the high corrosion-resistant cerium magnet is 500-3000ppm; the O content is 500-1000ppm, and the H content is 0-20ppm.

5. The method for preparing a highly corrosion-resistant cerium magnet according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. The ingredients are prepared according to the mass ratio of the components of the cerium alloy powder, and after removing surface impurities, the proportioned raw materials are placed in a quick-setting sheeting furnace, and the liquid raw materials are poured on a water-cooled copper roller at 1400-1500° C. to obtain a cerium alloy quick-setting sheet with a thickness of 0.2-0.6 mm, wherein the C content in the cerium alloy quick-setting sheet is ≤200ppm, and the O content is ≤150ppm; S2, adding the cerium alloy quick-solidification sheet into a hydrogen crushing furnace for coarse crushing to obtain cerium alloy coarse powder, and then adding it into a jet mill for further crushing to obtain cerium alloy powder; S3, preparing grain boundary modified powder according to proportion; S4, adding the grain boundary modified powder to the cerium alloy powder in proportion, and mixing them thoroughly and evenly, the mixing time is 2 to 10 hours; after the mixing is completed, let it stand for 2 to 4 hours; S5, magnetic field orientation molding and isostatic pressing: the mixed cerium alloy powder is added to a magnetic field press for orientation molding, the orientation magnetic field is 1.5-2.5T, and then isostatic pressing is performed at a pressure of 150-300MPa and a holding time of 10-50s to obtain a cerium magnet green body; S6. Sintering and tempering the cerium magnet green body.

6. The method for preparing a highly corrosion-resistant cerium magnet according to claim 5, characterized in that: In the step S2, the cerium alloy quick-setting sheet is added into the hydrogen crushing furnace for coarse crushing to obtain the cerium alloy coarse powder, which is specifically achieved under the following conditions: the hydrogen absorption temperature is 20-200°C, the hydrogen absorption pressure is 0.08-0.5MPa, the dehydrogenation temperature is 400-600°C, and the dehydrogenation time is 4-10h; the average particle size of the cerium alloy coarse powder after hydrogen crushing is 200-900μm, and the H content is ≤1500ppm.

7. The method for preparing a highly corrosion-resistant cerium magnet according to claim 5, characterized in that: The specific process of step S3 is: according to RE 2 The obtained alloy is pulverized by high-energy ball milling or airflow milling ultrafine powder collector, and the obtained alloy powder is successively oxidized, hydrogenated, and mixed with a lubricant containing C to obtain a composition of RE 2 a1 M b1 O c1 H d1 C e1 Grain boundary modified powder.

8. The method for preparing a highly corrosion-resistant cerium magnet according to claim 5, characterized in that: The step S6 comprises the following steps: S6.

1. Place the cerium magnet green body into a vacuum sintering furnace for sintering heat treatment. First, keep it at 200-400℃ for 1-4h for decarburization treatment, then keep it at 600-900℃ for 2-10h for dehydrogenation treatment, and finally carry out sintering densification treatment at 1020-1100℃ for 2-10h. Then, turn on the fan to fill in inert gas and cool it to below 200℃. S6.

2. Carry out the first tempering in a vacuum or inert gas atmosphere, keep it at 400-950℃ for 2-10 hours, and quickly cool it to below 70℃ before taking it out of the furnace; according to actual needs, carry out the second tempering, keep it at 400-950℃ for 2-10 hours, and quickly cool it to below 70℃ before taking it out of the furnace to obtain highly corrosion-resistant cerium magnets.

Citation Information

Patent Citations

  • Ce-based permanent magnet material with high corrosion resistance and preparation method thereof

    CN108666065A